How is the COVID-19 Crisis Affecting Nitrogen Dioxide Emissions in Sub-Saharan Africa? - Masaki, Takaaki; Nakamura, Shohei; Newhouse, David (World Bank, Washington, DC, 2020)
Daily estimates of Nitrogen Dioxide (NO2)—one of a group of pollutant gases that derive from human activity, primarily combustion—can provide a useful, albeit "noisy", real-time proxy measure of how COVID-19 has affected economic activity. To examine how the crisis affects NO2 levels in Sub-Saharan Africa (SSA), we calculated mean daily NO2 tropospheric estimates for 43 regions that contain either national capitals or large urban areas for the period July 2018 to April 2020. We found that emissions reductions in April were sizeable, larger in more developed areas, and large in many but not all of the countries that implemented national lockdowns. Overall, the data suggest that NO2 readings contain useful information to help track the reduction in motorized transport, and possibly overall economic activity, in urban, developed areas.